Altered perineal microbiome is associated with vulvovaginitis and urinary tract infection in preadolescent girls. (December 2014) - Gorbachinsky, Ilya; Sherertz, Robert; Russell, Gregory; Krane, L Spencer; Hodges, Steve J.
Background: Vulvovaginitis has a known association with urinary tract infections (UTIs) in girls. We hypothesize that vulvovaginitis is a major contributor to UTIs in prepubertal girls by increasing periurethral colonization with uropathogens. Methods: Periurethral swabs and urine specimens were obtained from a total of 101 girls (58 with vulvovaginitis and 43 without vulvovaginitis). Specimens were cultured for bacterial growth. The dominant organism in the periurethral swabs and urine cultures was recorded and antibiotic sensitivity profiles were compared. Results: Periurethral swabs from children with vulvovaginitis were associated with a statistically significant increase in uropathogenic bacteria (79% Enterococcus species or Escherichia coli ) as the dominant culture compared with swabs from girls without vaginitis (18%) ( p  < 0.05). In children with vulvovaginitis, 52% of the urine cultures were positive for UTIs, and the dominant organism in the urine cultures matched the species and antibiotic sensitivity profile of the corresponding periurethral swab. Only 11% of the urine cultures from girls without vulvovaginitis were positive for UTIs. Conclusions: Vulvovaginitis may cause UTIs by altering the perineal biome such that there is increased colonization of uropathogens.